ANALISIS PENGARUH PEMANFAATAN ABU TERBANG DAN ABU SEKAM PADI TERHADAP KUAT TEKAN BETON RINGAN - Khaerul Rijal; Sukandi (SANGKAREANG, 2018)
Light weight concrete is generally consists of lime stone, sand, silica, cement and water. Increasing demand and limited material resources lead to an expensive price and production. One of alternative materials which will be used to replace lime stone, silica and cement is the usage of fly ash and husk rice ash since they contain pozollan and silica. The usage of the above alternative materials as concrete forming materials contributes positive impact toward the environment in term of waste utilization. The character similarities enable fly ash and husk rice ash to be alternative material to reduce the amount of cement, lime stone and silica as light weight concrete’s forming materials, which has adequate pressure power. This research aims to find out the impact of the utilization of the waste of fly ash and husk rice ash toward pressure strength of light weight concrete. Sample of fly ash which used as research object is taken from the waste of coal combustion in PLTU (steam energy power plan) Jeranjang, West Lombok. Method applied in this research is pressure strength and weight content test in the laboratory. It resulted that the usage of fly ash material in the composition mixing of light weight concrete 0 -70 percent do not effecting the quality of light weight concrete since it equivalent to SNI or Indonesia’s national standard of pressure strength value of 22.08 kg/ cm2 – 43.37> 21 kg/cm2 . Moreover, husk rice material can be used as cement replacer material with minimum pressure strength value of 23.557 kg/ cm2 which contain 90 percent of husk rice material.